CORPORATE LIABILITY FORMULATION POLICY ACCORDING TO ARTICLE 101 OF LAW NUMBER 31 OF 2004 JUNCTO LAW NUMBER 45 OF 2009 CONCERNING FISHERIES IN TERM OF CRIMINAL LEGAL REFORM IN INDONESIA - Vivi Tri Kasih; Antory Royan Adyan; Herlambang Herlambang (Bengkoelen Justice : Jurnal Ilmu Hukum, 2021)
The corporation is the brain and source of funds for all illegal fishing activities and other crimes that occur along the chain of fishing business activities. According to Law Number 31 of 2004 in conjunction with Law Number 45 of 2009 concerning Fisheries, Article 101 states that: "In the case of a criminal acts as referred to in Article 84 paragraph (1), Article 85, Article 86, Article 87, Article 88, Article 89, Article 90, Article 91, Article 92, Article 93, Article 94, Article 95, and Article 96, the acts are committed by corporations; prosecution and criminal sanctions are imposed on their management and the fine is added by 1/3 (one third) of the sentence imposed." It is necessary to renew the Fisheries Law in order to provide an overview in determining the Corporate Liability Formulation Policy according to Article 101 of Law Number 31 of 2004 in conjunction with Law Number 45 of 2009 concerning Fisheries in the context of Criminal Law Reform in Indonesia. The type of this research was normative by using primary, secondary and tertiary sources of legal materials. From the results of research and discussion, it was revealed that Corporate Liability according to Article 101 of Law Number 31 of 2004 in conjunction with Law Number 45 of 2009 concerning Fisheries in Indonesia currently does not explain things about the meaning of the word "management", which parties in the management structure of a corporation that can be held accountable, or to what extent the authority possessed by parties in the management structure of a corporation can be subject to criminal responsibility. Therefore, the Corporate Liability Formulation Policy according to Article 101 of Law Number 31 of 2004 in conjunction with Law Number 45 of 2009 concerning Fisheries in the context of Criminal Law Reform in the future should be changed, this is important considering the formulation stage is the most strategic stage in the efforts to prevent and to control crime by including / expanding criminal liability, not only for the management but also for the corporation and its management.